Impact of New Technologies in Energy on Households - Novák, Dominik; Strouhal, Jiří, 1980-; Žádník, Josef; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
This masters thesis aims to assess and evaluate the potential of home based energy storage systems for the final user. In theoretical part it therefore describes the historical development of the European power sector with the purpose of determining, what was the impact of this development on products offered by energy providers to the final consumers of electricity. Findings from this analysis are then used to design a model, which is introduced and described in the practical part of the masters thesis. This model is afterwards used to assess the profitability of home batteries implementation by three different types of households and also to determine, what are the key drivers and constraints for the adoption of energy storage systems by households.
Vedoucí práce: Jiří Strouhal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses